A simultaneous investigation of the environmental Kuznets curve for the agricultural and industrial sectors in China. Issue 1 (2nd January 2023) - Moriwaki, Shota; Shimizu, Masayuki
Abstract: We investigate the relationship between China's high growth and environmental pollution from the agricultural and industrial sectors by estimating the environmental Kuznets curve (EKC). We used panel data of Chinese cities at the prefecture level and above for the period between 2011 and 2015 and estimated the EKC models using the system generalized method of moments (GMM). We found that agricultural chemical oxygen demand (COD) and industrial wastewater depict N-shaped and reverse N-shaped curves. Further, an EKC for agricultural nitrogen balance has been established. We find that industrial sulfur dioxide (SO2 ) emissions and their emission intensity support the EKC hypothesis. Our research is then used to provide policymakers with guidance on mitigating environmental pollution by comparing and scrutinizing the characteristics of agricultural and industrial pollution in China.